Asymmetric credit growth and current account imbalances in the euro area - Robert Unger (FIW - Research Centre International Economics, 2016)
The euro area crisis is often linked to the emergence of current account imbalances. As most of the deficit countries experienced pronounced credit booms at the same time that these imbalances were building up, this paper investigates the link between domestic credit developments and the current account balance. Using a panel error correction specification, the estimation results show that flows of bank loans to the non-financial private sector are a significant determinant of the current account and that they - together with changes in competitiveness - constituted the most important factor driving the build-up of current account imbalances in the deficit countries. Accordingly, impeding an increase in private sector indebtedness seems to be a promising way to dampen the formation of unsustainable current account imbalances.
Keywords: E50; F32; F45; G21; 330; banks; credit growth; current account imbalances; euro area